James Milnor papers - Milnor, James, 1773-1845.
Ten ALS (1811 November 28-December 14), written in Washington, D.C., by Milnor while serving as a Federalist member of Congress from Pennsylvania, to Thomas Bradford, Jr., of Philadelphia, Pa. Topics include matters before the House Foreign Relations Committee (Committee on Foreign Affairs), particularly the looming war with Great Britain and Masonic affairs.
U.S. representative from Pennsylvania, lawyer, and later, an Episcopal clergyman in Philadelphia, Pa., and New York, N.Y. Variant spelling James Milner.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bradford, Thomas, -- 1781-1851 -- Correspondence; Federal Party (U.S.); United States. -- Congress. -- House. -- Committee on Foreign Affairs; Freemasons; Great Britain -- Commerce -- History -- 19th century; Great Britain -- Foreign relations -- United States; Pennsylvania -- Politics and government -- 1775-1865.; Philadelphia (Pa.) -- History; United States -- Foreign relations -- Great Britain; United States -- Commerce -- History -- 19th century; United States -- History -- War of 1812.; Washington (D.C.) -- History; Clergy; Lawyers; Representatives, U.S. Congress -- Pennsylvania